PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN BAGIAN POTS DI BANDAR UDARA I GUSTI NGURAH RAI BADUNG BALI - Agung Eko Setiono (STIE BIITM, 2019)
The title of this research is the influence of competence and commitmen of the organization of the performance of employees in the POTS section at I Gusti Ngurah Rai Airport Badung – Bali. The formulation of the problems is whether competence has a partial positive effects on the performance of POTS section employees at I Gusti Ngurah Rai Airport Badung – Bali and does the organizational commitment have a partial positve and simultaneously affect the performances of POTS section employees at I Gusti Ngurah Rai Airport Badung - Bali This research aimed to determine the effect of competence and organizational commitment on POTS section employees’ performance at I Gusti Ngurah Rai Airport Badung – Bali. Also to determine the effect of competency and organizational commitmen on the performances of POTS employees. The analysis technique used is quantitative data validity and reliability test, classic assumption tes, multiple linear regression analysis, multiple correlation analysis, analysis of determination, T test and F test. Data collection method in this research using observation, documentation and questionnaries. The results of T test show the Competency vatiable has a positive and significant effect partially on employee performance, a significant effect is indicated by the calculation of t-count of 7,502 and also indicated organizational commitmen has a positive and significant effect on employees performance, indicated by results of the calculation of t-count of 3.712.